Electronic structure of GaN nanotubes - Sodré, Johnathan M.; Longo, Elson [UNESP]; Taft, Carlton A.; Martins, João B.L.; dos Santos, José D. (Cellule MathDoc/Centre Mersenne, 2017)
Nanotube properties are strongly dependent on their structures. In this study, gallium nitride nanotubes (GaNNTs) are analyzed in armchair and zigzag conformations. The wurtzite GaN (0001) surface is used to model the nanotubes. Geometry optimization is performed at the PM7 semiempirical level, and subsequent single-point energy calculations are carried out via Hartree–Fock and B3LYP methods, using the 6-311G basis set. Semiempirical and ab initio methods are used to obtain strain energy, charge distribution, dipole moment, |HOMO-LUMO| gap energy, density of states and orbital contribution. The gap energy of the armchair structure is 3.82 eV, whereas that of the zigzag structure is 3.92 eV, in agreement with experimental data.
Keywords: Ab initio; Density of states; DFT; Electronic properties; Gallium nitride nanotubes; Orbital contribution